Ectoparasites of Nile tilapia (Oreochromis niloticus) in cage farming in a hydroelectric reservoir in Brazil - Zago, Aline Cristina [UNESP]; Franceschini, Lidiane [UNESP]; Garcia, Fabiana; Canello Schalch, Sergio Henrique; Gozi, Katia Suemi; Silva, Reinaldo José da [UNESP] (Brazilian Coll Veterinary Parasitology, 2014)
For this study, we performed a parasitological analysis of cage-cultured Nile tilapia (Oreochromis niloticus) from the Agua Vermelha Reservoir, Southeastern Brazil, and verified relationships with limnological data, seasonality, and fish growth phase. From March 2010 to March 2011, sixty-three specimens of O. niloticus in three growth phases (i.e., initial, intermediate, and final) were collected. All fish specimens were infested with at least one ectoparasite species (prevalence = 100%). Five species of protozoans (Trichodina compacta, Trichodina magna, Ichthyophthirius multifiliis, Piscinoodinium pillulare, and Epistylis sp.) and five species of monogenoids (Cichlidogyrus halli, Cichlidogyrus thurstonae, Cichlidogyrus sp. 1, Scutogyrus longicornis, and Gyrodactylus sp.) were observed. The abundance of Trichodina spp. and the prevalence of Epistylis sp. were higher in the dry season, and the prevalence of C. halli was higher in the rainy season. For the majority of ectoparasites found in this study, fish in the intermediate and final phases had higher parasitism rates than those in the initial phase. The data presented may help fish farmers to understand the parasite dynamics of the fish species studied in cage-farming systems.

O presente estudo teve como objetivo realizar análise parasitológica de tilápias-do-Nilo, (Oreochromis niloticus) criadas em tanques-rede no Reservatório de Água Vermelha, Sudeste do Brasil, bem como verificar suas inter-relações com as características limnológicas, sazonalidade e fase de criação. Durante o período de março de 2010 a março de 2011, espécimes de O. niloticus, pertencentes a três fases de criação (inicial, intermediária e final), foram colhidos, totalizando 63 indivíduos. Todos os peixes estavam infestados por pelo menos uma espécie de ectoparasita (prevalência = 100%). Foi observada a ocorrência de cinco espécies de protozoários (Trichodina compacta, Trichodina magna, Ichthyophthirius multifiliis,Piscinoodinium pillulare e Epistylissp.), assim como cinco espécies de monogenóides (Cichlidogyrus halli, Cichlidogyrus thurstonae, Cichlidogyrus sp. 1,Scutogyrus longicornis e Gyrodactylussp.). A abundância de Trichodina spp. e prevalência de Epistylis sp. foram maiores no período seco, e a prevalência de C. halli foi maior no período chuvoso. Para a maioria dos ectoparasitas encontrados neste estudo, os peixes pertencentes às fases intermediária e final apresentaram maiores taxas de parasitismo do que aqueles pertencentes à fase inicial. Os dados apresentados neste estudo podem ser de grande importância para piscicultores, de forma a auxiliá-los no conhecimento da dinâmica dos parasitas da espécie de peixe estudada em sistemas de tanques-rede.
Ectoparasitas de tilápias-do-Nilo (Oreochromis niloticus) criadas em tanques-rede em um reservatório de usina hidrelétrica no Brasil
Keywords: Fish farming; Health; Water quality; Monogenoid; Trichodina spp.; Ichthyophthirius multifiliis; Piscicultura; Sanidade; Qualidade da água; Monogenóide; Trichodina spp.; Ichthyophthirius multifiliis